The Globalization of Social Movements: Exploring the transnational paradigm through collection action against neoliberalism from Latin America to the Occupy movement - Rachel McKane (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
The main thrust of this paper is that social movement theories, which have traditionally conceived of the various aspects of social movements through the lens of the nation-state, would do well to further adopt and integrate a transnational paradigm. The paper examines anti-neoliberal social movements, and the case of the Occupy movement in particular as an illustration that we cannot make sense of the emergence, actors, strategies, tactics, or goals of social movements without incorporating the context and salience of transnationalism in today’s global landscape. The paper attempts to justify the above thesis by demonstrating the nuanced linkages, similarities, and dissimilarities between the collective actions across Latin America (the Landless Workers’ Movement in Brazil and the Zapatista Movement in Mexico), the Global Justice Movement, and the Occupy movement. The hopeful novelty presented in this paper is that an intricate analysis of the Occupy movement makes clearer than ever before the significance of transnationalism in understanding contemporary social movements. It is through the specifics of the Occupy movement, which are given particular emphasis, that we can further refine the proper role of transnationalism in social movement theory. The movements assessed in this paper, connected by grievances brought on by neoliberal globalization, can be conceived as part of a web of spatiotemporal relations. However, movements may still be very nationalistic and dependent on culture. It is important to recognize transnational aspects when analyzing social movements, but also make distinctions between and within various movements.